Antimicrobial susceptibility patterns of pathogens isolated from clinical specimens at a tertiary care hospital in Bangladesh, 2020–2023 - Mohammad Kamruzzaman; Fahim Alam Nobel; Saiful Islam; Amiyo Haider; Mohammad Nasir Uddin; Mohammod Johirul Islam (The Microbe)
Antimicrobial resistance has emerged as a critical issue in the medical sector globally, including in developing countries such as Bangladesh. The objective of the study was to determine the profile of bacteria and antibiotic resistance patterns of various clinical specimens at a tertiary care hospital in Mymensingh, Bangladesh from January 2020 to December 2023. In this study, a total of 2068 samples were collected from various clinical specimens, such as ear, wound, throat, urine, and pus, following standardized collection procedures. The isolates were characterized through colony morphology, gram staining, and biochemical assays. Their antibiotic susceptibility patterns were determined using the Kirby-Bauer disk diffusion method. Out of 2068 isolates, 644 (31.1 %) were gram-positive and 1424 (68.9 %) were gram-negative bacteria. Isolates belonged to males (55.3 %) and females (44.7 %). The most common gram-negative bacterial isolates were Pseudomonas spp. (33.9 %) and Escherichia coli (23.4 %), whereas the most common isolates of gram-positive bacteria were Staphylococcus spp. (15.8 %) and Streptococcus spp. (12.2 %). Among gram-positive bacteria, resistance was highest to Penicillin-G (92 %) and Colistin (90.8 %). Gram-negative bacteria showed the highest resistance to Colistin (83.3 %) and Cefuroxime (82.1 %). The majority of the isolates were resistant to multiple antibiotics (≥3), with 83.4 % being multidrug-resistance (MDR), 8.7 % extensively drug-resistance (XDR), and 0.6 % pan-drug resistance (PDR). Given the rising antimicrobial resistance in Bangladesh, regular surveillance to monitor bacterial patterns and antibiotic sensitivity is essential for developing local antibiograms, which can guide physicians in effectively treating infections.